2020
DOI: 10.1038/s41586-020-2421-7
|View full text |Cite
|
Sign up to set email alerts
|

A remnant planetary core in the hot-Neptune desert

Abstract: The interiors of giant planets remain poorly understood. Even for the planets in the Solar System, difficulties in observation lead to major uncertainties in the properties of planetary cores. Exoplanets that have undergone rare evolutionary pathways provide a new route to understanding planetary interiors. We present the discovery of TOI-849b, the remnant core of a giant planet, with a radius smaller than Neptune but an anomalously high mass M p =40.8 +2.4 −2.5 M ⊕ and density of 5.5 ± 0.8 gcm −3 , similar to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 134 publications
2
40
0
Order By: Relevance
“…TOI 849-A dense and unusually massive planet ( ), TOI 849 b is considered a planetary core of a hot Jupiter (Armstrong et al 2020). Of further interest is that TOI 849 b resides in the hot-Neptune "desert," a region in exoplanet mass-radius period parameter space that contains few planets.…”
Section: Some Notable Tess Exoplanetsmentioning
confidence: 99%
“…TOI 849-A dense and unusually massive planet ( ), TOI 849 b is considered a planetary core of a hot Jupiter (Armstrong et al 2020). Of further interest is that TOI 849 b resides in the hot-Neptune "desert," a region in exoplanet mass-radius period parameter space that contains few planets.…”
Section: Some Notable Tess Exoplanetsmentioning
confidence: 99%
“…The QLP has already been used to identify and alert planet candidates throughout the entire TESS Primary Mission, leading to the discovery of more than 1000 planetary candidates (Guerrero et al 2020, submitted to ApJS ), dozens of which have already been confirmed(e.g. Huang et al 2018b;Vanderspek et al 2019;Huang et al 2020;Armstrong et al 2020). Here, we describe how QLP produces light curves and evaluate its performance in terms of photometric precision.…”
Section: Introductionmentioning
confidence: 99%
“…Large exoplanets with unusually high densities such as Kepler-36b, NGTS-4b, and TOI-849b have been recently discovered and interpreted as the remnant cores of gas giants [39][40][41] . Several hypotheses have been proposed: (i) these planets once had a thicker atmosphere and suffered massive loss of their atmospheric H, or (ii) they were not able to accrete dense atmospheres either because of late formation or formation in a region of the protoplanetary disk devoid of gas 41 . Our study suggests the alternative possibility of H storage in the core.…”
Section: Discussionmentioning
confidence: 99%
“…TOI-849b and NGTS-4b require a thin atmosphere to explain their radii 41 . Although efficient packing would make FeH x much more dense than separate Fe and xH, the density of the H-bearing core would be less than that of a pure Fe core and the mass-radius relation approaches that of MgSiO 3 bridgmanite as the bulk H content of the planet increases (Fig.…”
Section: Discussionmentioning
confidence: 99%